Membangun Loyalitas Merek: Strategi Efektif Produk Low Voltage pada Konsumen B2B - Siregar, Bintang Eska Putra; Adiwijaya, Karto (Fakultas Ekonomi dan Bisnis Universitas Samudra, 2025)
This study aims to analyze the strategy used by Schneider's low-voltage brand products for sales to B2B consumers. This study uses an in-depth interview method, which is conducted with sources including Schneider representatives and exclusive distributors and retail distributors. The study protocol as a reference for questions conducted in this interview is based on the strategy factor for building brand loyalty. The results provide insight into how low-voltage products build brand loyalty with distributors so that there is a decision to repeat the purchase of the Schneider brand and work together in the long term. This study contributes as an analysis to Schneider to be able to improve its service to distributors, so that it can maintain good loyalty with distributors. The novelty of this study is the addition of strategy factors that build brand loyalty.